Social Media-Induced Cyber Bullying Behaviour Affecting Teenagers - Alvian Pradana Ambarita; T. Riza Zarzani (International Journal of Sociology and Law, 2024)
Cyberbullying is bullying using digital technology. This can happen on social media, chat platforms, gaming platforms, and mobile phones. Meanwhile, according to Think Before Text, cyberbullying is aggressive and purposeful behavior carried out by a group or individual, using electronic media, repeatedly from time to time, against someone who is deemed not to easily resist this action. So, there is a difference in power between the perpetrator and the victim. The difference in strength in this case refers to a perception of physical and mental capacity. The nature of the research used is normative legal research and the data collection method used in this research is secondary data obtained through library research, namely by conducting research on various literature such as books, laws, with the aim of to look for concepts, or understandings related to the problem of Cyber ​​Bullying Behavior Due to Social Media Which Affects Teenagers. The physical impact of cyberbullying is that teenagers experience headaches, stomach aches, sleep disorders, fatigue, back pain, loss of appetite and digestive problems. Psychologically and emotionally, teenagers feel fear, feelings of terror, anxiety, suffering, sadness, stress and symptoms of depression. School is related to teenagers being less motivated to go to school and a decrease in concentration levels or academic grades. Psychosocially, adolescents have feelings of isolation and loneliness, exclusion and even social rejection. That a personality who is dominant and enjoys violence tends to be temperamental, impulsive, and easily frustrated and often behaves aggressively in adults. Personality characteristics have a fairly high role in a person's tendency to become a perpetrator of cyberbullying. A person with high self-esteem will show himself to have power over others. This is what makes cyberbullying perpetrators show that they are someone who is powerful by bullying weak people.